ASSESSMENT OF THE FINANCIAL CONDITION OF RUSSIAN BANKS AND WAYS TO IMPROVE - O. S. Dyakonova; N. V. Kovaleva (Вестник университета, 2020)
The indicators, necessary for the improvement of the system of assessment of the financial condition of the banks of Russia, have been analyzed. The reasons of inefficient assessment of the bank’s activity results and the resulting negative consequences have been considered. The hypothesis about the necessity of application of methods of forecasting at acceptance of strategically important administrative decisions and expert estimation of a current situation for avoidance of the critical situations, leading to bankruptcy and insolvency in the sphere of bank activity has been put forward. The main causes of crisis situations occurrence, taking into account the dynamics of external and internal indicators, have been considered. A list of indicators, consisting of two groups that should be taken into account when assessing the financial condition of Russian banks, has been presented. Despite the apparent transparency of the indicators under study, a practical problem of forming a single methodology arises, that would lead to a significant increase in the adequacy of assessment of the performance of Russian banks.